Maulid Nabi Prophet Maulid as a Measurement of Tonggara Village Communities in Worship - Laela Nurdiani Nurdiani; Rizqiyatul Khasanah; M. Adin Setyawan (Fakultas Pertanian, Universitas Samudra, 2023)
Maulid tradition is a reminder of the Birthday of the Prophet Muhammad. For the people of Desa Tonggara, this tradition is held as a celebration to increase people's understanding of Islam, strengthen faith in Allah SWT, love of the Prophet Muhammad and strengthen the sense of brotherhood that foster social solidarity among Muslims. The celebration of the birthday of the Prophet Muhammad SAW is a necessity in society and is celebrated every year based on a culture that has been passed down for generations. The purpose of the study is to study and analyze solidarity in the tradition of maulids formed through shared interests based on moral feelings and beliefs held. This research uses a qualitative approach with descriptive methods. Data analysis techniques based on interpretation of primary and secondary data. The results showed the celebration of the tradition of maulid is a culture in Acehnese society that is based on religious values reinforced by the solidarity ties of the whole community. Solidarity that occurs is manifested in the form of solidarity regardless of social status and cooperation between communities in maintaining the existence of tradition until now.